2013
DOI: 10.1111/edt.12079
|View full text |Cite
|
Sign up to set email alerts
|

Management of crown‐related fractures in children: an update review

Abstract: -Traumatic dental injuries (TDIs) are a serious public health problem. Epidemiology of dental trauma indicates that these injuries are more prevalent in child population of the world. Children are the sufferers in two-thirds of all TDIs observed. Although being a major fraction, crown-related fractures are a less severe form of TDIs with respect to their complications and sequelae. However, as with other types of traumatic injuries, the delay in seeking for immediate care following a traumatic injury and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 172 publications
(279 reference statements)
1
35
1
4
Order By: Relevance
“…This condition could have ranked in the fifth place after caries, headache, anemia, and hearing loss, if considered and listed among the main chronic diseases and injuries by the GBD study 2015 . After dental caries, TDI is the second most frequent oral disease preceding periodontal disease and severe tooth loss …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition could have ranked in the fifth place after caries, headache, anemia, and hearing loss, if considered and listed among the main chronic diseases and injuries by the GBD study 2015 . After dental caries, TDI is the second most frequent oral disease preceding periodontal disease and severe tooth loss …”
Section: Introductionmentioning
confidence: 99%
“…TDIs usually affect a single tooth, however, on occurrence of certain traumatic events such as sports, violence, and traffic accidents, multiple tooth injuries can arise . Maxillary central incisors are the most frequently affected teeth in both primary and permanent dentitions .…”
Section: Introductionmentioning
confidence: 99%
“…Traumatske povrede čvrsih zubnih tkiva kao što su frakture gleđi retko su praćene komplikacijama [8]. Za razliku od njih frakture gleđi i dentina su opsežnije povrede sa većim rizikom za nastanak komplikacija.…”
Section: Uvodunclassified
“…U literaturi, frakture gleđi i gleđi i dentina bez eksponiranja pulpe označavaju se kao nekomplikovane. Frakture gleđi, nekomplikovane frakture gleđi i dentina i luksacije najčešće su povrede stalnih zuba [7].Traumatske povrede čvrsih zubnih tkiva kao što su frakture gleđi retko su praćene komplikacijama [8]. Za razliku od njih frakture gleđi i dentina su opsežnije povrede sa većim rizikom za nastanak komplikacija.…”
unclassified
“…Although oral region only constitutes 1% of the body, it is most effect of the body after trauma [1]. Epidemiological studies have reported that pre-school children are exposed to dental trauma rate of 6.1%-62.1% and approximately 25% of all children below the age of 18 years are exposed to trauma in anterior teeth [2][3][4].…”
Section: Introductionmentioning
confidence: 99%